A retrospect of ozone formation mechanisms during the COVID-19 lockdown: The potential role of isoprene. (15th January 2023) - Xu, Kai; Liu, Yafei; Li, Feng; Li, Chenlu; Zhang, Chen; Zhang, Huan; Liu, Xingang; Li, Qijie; Xiong, Min
Abstract: Wuhan took strict measures to prevent the spread of COVID-19 from January 26 to April 7 in 2020. The lockdown reduced the concentrations of atmospheric pollutants, except ozone (O3 ). To investigate the increase in O3 during the lockdown, trace gas pollutants were collected. The initial concentrations of volatile organic compounds (VOCs) were calculated based on a photochemical ratio method, and the ozone formation potential (OFP) was obtained using the initial and measured VOC concentrations. The O3 formation regime was NOX -limited based on the VOCs/NOX diurnal ratios during the lockdown period. The reduced nitric oxide (NO) concentrations and lower wind speed (WS) could explain the night-time O3 accumulation. The initial total VOCs (TVOCs) during the lockdown were 47.6 ± 2.9 ppbv, and alkenes contributed 48.1%. The photochemical loss amounts of alkenes were an order of magnitude higher than those of alkenes in the same period in 2019 and increased from 16.6 to 28.0 ppbv in the daytime. The higher initial alkene concentrations sustained higher OFP during the lockdown, reaching between 252.4 and 504.4 ppbv. The initial isoprene contributed approximately 35.0–55.0% to the total OFP and had a positive correlation with the increasing O3 concentrations. Approximately 75.5% of the temperatures were concentrated in the range of 5 and 20 °C, which were higher than those in 2019. In addition to stronger solar radiation, the higher temperatures induced higher isoprene emission rates, partially accounting for the higher isoprene concentrations. Lower isoprene-emitting trees should be considered for future urban vegetation to control O3 episodes. Graphical abstract: Image 1 Highlights: The ozone formation regime during the lockdown in Wuhan was NOX -limited. Alkenes contributed 48.1% to the initial total VOC concentrations during the day. Initial isoprene contributed 35%–55% to the ozone formation potential (OFP). OFP derived from initial isoprene was positively correlated with ozone concentrations. Higher air temperatures lead to increased emissions of isoprene.